Cytohistopathological appraisal of unusual locations of epidermoid inclusion cysts - Mujawar, Parvez; B. Nikumbh, Dhiraj; V. Dravid, Nandkumar; Prabhat, Ravi (International Surgery Journal, 2018)
Background: Epidermoid inclusion cysts are common benign lesions of the pilosebaceous origin that encountered anywhere in the body. Most common sites are hairy and non hairy areas mainly scalp, back, neck and trunk. Objective of present study was to highlight and document the cytohistomorphological features of epidermoid inclusion cysts (EIC) at unusual locations of the body in our tertiary care center. Methods: The present study is retrospective, cross sectional study done on cytohistopathological specimen over a period of 30 months from June 2016 to December 2017. A total of 82 cases of EIC were included in the study. All the sites were included in the study that is usual as well as unusual. Sebaceous and dermoid cysts were excluded from the study. Unusual sites of EIC were collected, tabulated and compared with existing literature. Results: The most common affected site of EIC in our study was head, neck and face (42.7%) followed by extremities and axilla (29%), back (11%) and chest/abdomen (8.6%). Peak incidence of EIC was found in 31 to 40 years (34.1%) with male preponderance (1.5:1). The unusual sites encountered were oral cavity and tonsil in head neck region, sole in the extremities, breasts and testis. Conclusions: The study highlights the importance of FNAC in early diagnosis and histopathology for confirmation and treatment purposes in epidermoid inclusion cysts. It provides prompt response to avoid cosmetic and functional disabilities in unusual locations of common lesions like EIC because the differentials may from inflammatory to malignant ones.